Penilaian kaedah laluan terpendek : rangkaian jalan raya kajian kes : Negeri Johor dan Melaka - Ramlan, Rohaizan (2005)
Modern technology that is used to find the shortest path had clear up problems like finding the shortest path between the two location. Random networking, which didn’t have th e exact road network, is used in most of the shortest path’s research. There are vari ous classical methods that are used to find the shortest path. Some of it are Djikstra, Floyd-Warshall and Bellman-Ford. But every method has it’s restriction and advantage to im plement for the exact road networking. Assessment will be done by calculate the algorithm complexion and runtime using the computer. From the assessment, a proper method is found in order to find Johore’s and Malacca’s shortest path road networking.